2019
DOI: 10.36552/pjns.v23i3.364
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Endoscopic Discectomy in Patients with Lumbar Prolapsed Intervertebral Disc

Abstract: Objective: To determine the outcome of endoscopic discectomyin patients with lumbar prolapsed intervertebral disc in terms of back pain and leg pain using the visual analogue scale.Material and Methods: Descriptive case series, was conducted at, PINS, LGH Lahore for 6 months. 15 patients were included through non probability consecutive sampling that fulfilled inclusion criteria. All patients’ low back pain and leg pain was documented using visual analogue scale before and after 2 months of surgery.On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…16,17 A study conducted in Pakistan by Sheikh et al reported good results in 84%, and satisfactory results in 16%, while there was no patient with poor results. 18 Previously conducted study in Nepal by Yadav et al reported very good and satisfactory results in 70.6% cases while poor results were noted in 15.7% cases. 19 A study conducted in Iraq reported back pain in 73.7% and lower limb radiating pain in 56.3% cases.…”
Section: Discussionmentioning
confidence: 92%
“…16,17 A study conducted in Pakistan by Sheikh et al reported good results in 84%, and satisfactory results in 16%, while there was no patient with poor results. 18 Previously conducted study in Nepal by Yadav et al reported very good and satisfactory results in 70.6% cases while poor results were noted in 15.7% cases. 19 A study conducted in Iraq reported back pain in 73.7% and lower limb radiating pain in 56.3% cases.…”
Section: Discussionmentioning
confidence: 92%